Gangguan Psikotik Lir-Skizofrenia (Schizoprenia-Like) Akut - Rizky Ananda Tanjung (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Acute Schizophrenia-like Psychotic Disorder (ICD-10 code F23.2) is a psychotic condition characterized by symptoms such as hallucinations, delusions, and disorganized thinking that resemble schizophrenia, but with a rapid onset and shorter duration. This case involves a 38-year-old male who exhibited sudden behavioral changes, including persecutory delusions, hallucinations, and aggressive behavior, which occurred over the past week. The diagnosis was made after ruling out possible medical or toxicological causes for the symptoms. Supporting laboratory tests showed normal results, with negative findings for substance abuse and SARS-CoV-2 infection. Management included risperidone as the primary antipsychotic and diazepam for anxiety relief, accompanied by psychosocial approaches and family education. The patient’s prognosis is relatively good with early intervention, although further monitoring is required to prevent the potential progression to chronic psychotic disorders. This case study emphasizes the importance of early diagnosis and a multidisciplinary approach in managing acute psychotic disorders to prevent long-term complications.